TOI-220 b: a warm sub-Neptune discovered by TESS. Issue 3 (22nd May 2021) - Hoyer, S; Gandolfi, D; Armstrong, D J; Deleuil, M; Acuña, L; de Medeiros, J R; Goffo, E; Lillo-Box, J; Delgado Mena, E; Lopez, T A; Santerne, A; Sousa, S; et al.
ABSTRACT: In this paper, we report the discovery of TOI-220  b, a new sub-Neptune detected by the Transiting Exoplanet Survey Satellite ( TESS ) and confirmed by radial velocity follow-up observations with the HARPS spectrograph. Based on the combined analysis of TESS transit photometry and high precision radial velocity measurements, we estimate a planetary mass of 13.8 ± 1.0 M⊕ and radius of 3.03 ± 0.15 R⊕, implying a bulk density of 2.73 ± 0.47 $\rm {g\, cm}^{-3}$ . TOI-220  b orbits a relative bright ( V = 10.4) and old (10.1 ± 1.4 Gyr) K dwarf star with a period of ∼10.69 d. Thus, TOI-220  b is a new warm sub-Neptune with very precise mass and radius determinations. A Bayesian analysis of the TOI-220  b internal structure indicates that due to the strong irradiation it receives, the low density of this planet could be explained with a steam atmosphere in radiative–convective equilibrium and a supercritical water layer on top of a differentiated interior made of a silicate mantle and a small iron core.